The AI Revolution in Medicine: Predicting, Preventing, and Curing Diseases with Artificial Intelligence - Joaquim Pinto (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the use of artificial intelligence (AI) in disease risk prediction and disease prevention through a systematic review of literature from 2019 to 2024. The research method used is an analysis of scientific articles published in international journals Scopus Q1. The research results show a significant increase in the use of AI in disease risk prediction, especially in the context of neurodegenerative diseases, cardiovascular conditions, cancer, and autoimmune diseases. The implications of this research include the potential of AI in improving the accuracy of disease risk predictions, providing timely interventions, and improving the clinical management of patients. However, the use of AI in disease risk prediction is also faced with various ethical challenges and impacts, including limited available health data, the complexity of AI models, complex interpretation of results, and privacy and fairness issues. The practical implication of this research is the need for a holistic and sustainable approach in the development and implementation of AI models in disease prevention, which takes into account the complex challenges and opportunities associated with the use of AI in health contexts.